An increase in stimulus arousal has differential effects on the processing speed of pleasant and unpleasant stimuli - Purkis, H.; Lipp, Ottmar; Edwards, M.; Barnes, R. (Springer Netherlands, 2009)
The arousal value of a stimulus influences its salience, whereby higher arousal should lead to faster processing. However, in previous research, participants consistently made faster valence judgments for low arousal, pleasant stimuli than for high arousal, pleasant stimuli. The speed of valence and arousal judgments for pictures and words were investigated in three experiments. Valence judgments were faster for low arousal than for high arousal pleasant pictures and for high arousal than for low arousal unpleasant pictures and words. Moreover, arousal judgments were faster for low arousal than high arousal pleasant and for high arousal than low arousal unpleasant pictures and words. The current research confirms that the impact of valence and arousal on processing speed does not reflect on the labels (valence versus arousal) used when recording speeded judgments. Similarly to valence, stimulus arousal interacts differentially with the evaluation of pleasant and unpleasant stimuli producing a processing advantage for high arousal, unpleasant stimuli but not high arousal, pleasant stimuli. © Springer Science+Business Media, LLC 2009.